2019
DOI: 10.1149/2.0181910jes
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Tungsten Carbide Nanosheets for Trace Level Detection of Toxic Mercury Ions in Biological and Contaminated Sewage Water Samples: An Electrocatalytic Approach

Abstract: In this work, we describe a facile synthesis of tungsten carbide nanosheets (WC NSs) via hydrothermal approach, and various analytical and electrochemical techniques were used for its characterized. Mercury (Hg II) is one of the most toxic elements that directly and indirectly affects human health and the environment. The optimization condition such as various pHs toward Hg(II) detection was studied. Consequently, in this study, we offer a selective and pico-molar Hg(II) electrochemical sensor in biological an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…2 presents the preparation of magnetic NiFe 2 O 4 -NPs and polypyrrole (PPy) nanocomposites used in the modification of a GCE for the determination of Pb 2+ in tap, lake, and river water samples. 96 Although the performance of the NM-modified electrodes has been mainly tested in real water samples, several studies reported on their use in heavy metal determination in other samples, including, among others, body fluids 31,57,88,163,173,190 and cosmetic product 190 samples. Moreover, Das et al 31 successfully employed a bimetal oxide (Bi 2 O 3 /Fe 2 O 3 )-NP decorated GO modified PGE for the determination of Cd 2+ in a wide range of real samples, including food (potato, lemon, and apple), soil, biological samples (blood serum and urine), and water (tap, drinking and chemical laboratory wastewater) samples.…”
Section: Nanomaterials As Electrode Modifiersmentioning
confidence: 99%
See 1 more Smart Citation
“…2 presents the preparation of magnetic NiFe 2 O 4 -NPs and polypyrrole (PPy) nanocomposites used in the modification of a GCE for the determination of Pb 2+ in tap, lake, and river water samples. 96 Although the performance of the NM-modified electrodes has been mainly tested in real water samples, several studies reported on their use in heavy metal determination in other samples, including, among others, body fluids 31,57,88,163,173,190 and cosmetic product 190 samples. Moreover, Das et al 31 successfully employed a bimetal oxide (Bi 2 O 3 /Fe 2 O 3 )-NP decorated GO modified PGE for the determination of Cd 2+ in a wide range of real samples, including food (potato, lemon, and apple), soil, biological samples (blood serum and urine), and water (tap, drinking and chemical laboratory wastewater) samples.…”
Section: Nanomaterials As Electrode Modifiersmentioning
confidence: 99%
“…Five main types of NMs, i.e. , graphene, graphene oxide (GO) and reduced graphene oxide (rGO), 22–92 NPs, 23–25,27,31,56,57,59,64,67,70,83,86,87,93–138 single and multiwalled carbon nanotubes (SWCNTs and MWCNTs), 32,83,89,98,99,101,113,129,133,139–162 nanosheets, 34,85,107,111,139,162–166 and nanofibers, 167–169 have been employed in the modification of the electrodes used in the determination of heavy metals. Nanocubes, nanoflakes, nanospheres, and nanodiamonds 75,170–175 are among the other types of NMs used in the modification of the electrodes.…”
Section: Nanomaterials As Electrode Modifiersmentioning
confidence: 99%
“…[66] Mercury ion (Hg 2 + ), one of the most toxic elements that affects the environment as well as human health, is very important to develop a trace-level mercury sensor for the detection of mercury contamination in water sources and seafood. [67] Several nanofibers based electrochemical sensors were reported [68] that they will be discussed in the following. Liao et al [68a] proposed a sensor based on a composite of CNF and bis(indolyl)methane (BIM) as a highly specific Hg 2 + complex-agent for anodic stripping analysis of Hg 2 + .…”
Section: Heavy Metal Detectionmentioning
confidence: 99%
“…Mercury ion (Hg 2+ ), one of the most toxic elements that affects the environment as well as human health, is very important to develop a trace‐level mercury sensor for the detection of mercury contamination in water sources and seafood [67] . Several nanofibers based electrochemical sensors were reported [68] that they will be discussed in the following.…”
Section: Developed Nf‐composites Modified Electrodes For Wastewater T...mentioning
confidence: 99%
“…One reason that WC has been used as the substrate is its similar bulk electronic properties to Pt-group metals. 9,[30][31][32] Furthermore, metal-modified WC electrocatalysts have proven increased CO tolerance. 33 The WC support has been postulated to help increase the dispersion of the metal nanoparticles.…”
mentioning
confidence: 99%